Harnessing Lactiplantibacillus plantarum EP21 and its membrane vesicles to inhibit myopia development - Chi-Fong Lin; Yu-An Hsu; Yung-Lan Chou; Ying-Chi Chen; En-Shyh Lin; Peng-Tai Tien; Jamie jiin-Yi Chen; Ming-Yen Wu; Chia-Hung Lin; Hui-Ju Lin; Lei Wan (Gut Microbes, 2025)
Lactiplantibacillus plantarum, a probiotic that is frequently found in fermented foods, is well known for its numerous health-enhancing properties. This study explored the potential of Lactiplantibacillus plantarum EP21 and its membrane vesicles (MVs) in mitigating myopia progression. In animal models of form-deprivation and TGF-β2-induced myopia, EP21 reduced axial elongation and refractive error shifts. EP21 administration suppressed retinal inflammation by inhibiting nuclear factor-κB activation and decreasing expression levels of tumor necrosis factor-α, NLR family pyrin-domain-containing-3, and interleukin (IL)-1β, while upregulating the expression of anti-inflammatory IL-10 in retinal tissues. To identify the molecular mechanism by which EP21 inhibits myopia, purified MVs were administered by intraperitoneal or intravenous injection or applied directly onto the ocular surface. The MVs crossed the blood – retinal barrier and accumulated in the outer segment of the retina. The MVs exhibited anti-myopic properties, indicated by a reduction in axial length elongation and a corresponding upregulation of refractive error. Mechanistic investigations revealed that EP21-MVs contain bacterial miRNAs that inhibit inflammatory responses and retinal structural remodeling. Furthermore, MV and its miRNAs upregulated genes that are associated with ubiquitination (TNF alpha-induced protein 3, TNFAIP3-interacting protein 1, and Tax1 binding protein 1), which are crucial for maintaining ocular proteostasis and regulating inflammation. EP21 administration, besides MV release, altered systemic metabolites, including tryptophan derivatives and short-chain fatty acids. The findings suggest a role of the gut – eye axis in the development of myopia and elucidate a biological pathway whereby gut-derived probiotics and their vesicles can influence ocular health. This research highlights the potential of EP21- and EP21-derived MVs as noninvasive agents for myopia management, and thereby enhances the comprehension of the gut – eye axis. By targeting inflammation and retinal remodeling, probiotics such as EP21 may contribute to addressing the global myopia epidemic, which offers a promising pathway for both preventive and therapeutic strategies.